Reliability and Mean Time to System Failure of a Parallel System' by Using One or Two Decimal Random Data Points - Kaur, H; Sharma, S K (EAI Endorsed Transactions on Scalable Information Systems, 2024)
Focusing on Weibull failure rules, which govern the stopping of components, this work evaluates reliability metrics such as stability and the mean time to system failure (MTSF) of a structure that is parallel. These metrics' behaviour has been seen for one or two decimal random values of component failure rates, operation times, form parameters, and the total quantity of components used in the parallel structure. In order to analyze the variation in the ethics of reliability as well as MTSF, the particular case of the Weibull distribution has also been taken up.
Keywords: Mean time to system failure; MTSF; Weibull distribution; Parallel system; Series system; Failure rate